The building blocks of the universe - John, Anslyn J. (HTS teologiese studies, 2021)
I review the state of knowledge of the composition of the universe for a non-specialist audience. The universe is built up of four components. These are radiation, baryonic (ordinary) matter, dark matter and dark energy. In this article, a quick outline of the theory of Big Bang nucleosynthesis is presented, and the origin of the elements is explained. Cosmology requires the presence of dark matter, which forms most of the mass of the universe, and dark energy, which drives the acceleration of the expansion. The dark sector is motivated, and possible explanations are stated.Contribution: As part of this special collection on building blocks, the building blocks of the universe are discussed and unsolved problems and proposed solutions are highlighted.